Biology of Polyphagotarsonemus latus (Banks, 1904) (Acari: Tarsonemidae) on cotton - Vieira, Marineide Rosa; Chiavegato, Luiz Gonzaga (Pesquisa Agropecuaria Brasileira, 1998)
Leaf discs obtained from the first or second non-cotyledonal leaf of cotton (Gossypium hirsutum L.) seedlings were used for the study of the biology of Polyphagotarsonemus latus on cotton IAC-20 cultivar. Seedlings were grown in pots and placed on a layer of cotton moistened with distilled water.The assays were carried out at 28.5 ± 0.3°C, relative humidity of 71.0 ± 2.6% and a 14 h photophase.The duration of immature phases was 4.1 ± 0.1 days for females and 4.1 ± 0.3 days for males, with a survival of 91.2%. After a pre-oviposition period of 1.1 ± 0.2 days, the females deposited 4.5 ± 0.9 eggs per day during 6.8 ± 1.3 days, i.e., 29.6 ± 7.3 eggs per female. The longevity was 10.0 ± 1.5 days for females and 8.8 ± 1.1 days for males. The intrinsic rate of increase (rm) was 0.323; finite rate of increase (λ) 1.38 individual per female per day; mean generation time (T) 9.54 days and net reproductive rate (Ro) 21.73.
Keywords: broad mite; biological development; net reproductive rate